The Role of Islamic Religious Education Teachers in Fostering the Habit of Congregational Prayer for Students - Aisah; Asy’ari, Hasyim; Rofiq, Muhammad Husnur (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to obtain objective data regarding the role of Islamic Religious Education (PAI) teachers in instilling the habit of congregational prayer at MIN 11 Banda Aceh. The main focus of this research is to examine how Islamic religious education is implemented at the school and to what extent teachers contribute to developing the habit of congregational prayer among students. The research employs an inductive qualitative method, with data collected through observations, interviews, document analysis, and questionnaires. The findings indicate that Islamic religious education at MIN 11 Banda Aceh has been implemented under the established curriculum. Its implementation includes the foundations of Islamic religious education, learning objectives, and teaching strategies designed to foster students’ religious character. In efforts to instill the habit of congregational prayer, PAI teachers play three main roles: as trainers, role models, and disciplinarians. Among these roles, only two have been effective—serving as trainers and role models. Meanwhile, the disciplinarian role has been less successful, as students are not subjected to sanctions for failing to perform congregational prayers. Nevertheless, the school has established a rule that when the zuhr adhan is called, all teaching and learning activities must be paused to allow students to perform congregational prayers.